Association of cardiovascular risk factors and intraplaque neovascularization in symptomatic carotid plaque - Liu, Zehao; Zhang, Lianlian; Sun, Bing; Ding, Yasuo (Frontiers in Neurology, 2024)
Background and purpose Cardiovascular risk factors are known to contribute to the formation of atherosclerotic plaques, which can result in carotid stenosis. However, the extent to which these factors are associated with intraplaque neovascularization, a key indicator of plaque vulnerability, remains unclear. To investigate this relationship, a study was conducted utilizing contrast-enhanced ultrasound (CEUS) to assess intraplaque neovascularization in symptomatic patients. Methods A cohort of 157 symptomatic patients underwent evaluation using Contrast-Enhanced Ultrasound (CEUS) imaging to assess carotid intraplaque neovascularization, which was quantified based on the degree of plaque enhancement. The collected data encompassed baseline patient characteristics, results from biochemical examinations, cardiovascular risk factors, and medication usage history. Regression analyses were conducted to elucidate the relationship between carotid plaque neovascularization and various cardiovascular risk factors. Results Patients with intraplaque neovascularization were more prone to have diabetes mellitus (OR 3.81, 95% CI 1.94–7.46, p < 0.001), dyslipidemia (OR 2.36, 95% CI 1.22–4.55, p = 0.011) and hypertension (OR 2.92, 95% CI 1.50–5.71, p = 0.002). Smoking increased the risk of having intraplaque neovascularization (OR 2.25, 95% CI 1.12–4.54, p = 0.023). Treatment with statins was significantly lower in patients with intraplaque neovascularization (OR 0.37, 95% CI 0.19–0.72, p = 0.003). In the multivariate analysis, diabetes mellitus (OR 3.27, 95% CI 1.10–9.78, p = 0.034) was independently related to the presence of intraplaque neovascularization. Meanwhile, compared to the patients in the first tertile of serum glucose (< 6.20 mmol/L), the patients in the third tertile (> 13.35 mmol/L) had the most significance of intraplaque neovascularization (OR 5.55, 95% CI 1.85–16.66, p = 0.002). Conclusion The findings indicated that diabetes mellitus is a significant cardiovascular risk factor that is strongly associated with carotid intraplaque neovascularization.